Search term “One Health” remains of limited use to identify relevant scientific publications: Denmark as a case study - Benedetti, Guido; Jokelainen, Pikka; Ethelberg, Steen (Frontiers in Public Health, 2022)
One Health has become a popular approach, and scientific advancements in the field should be easily findable and accessible to a wide range of relevant audiences, from researchers to policymakers, and across sectors. We conducted a systematic, narrative review of available scientific publications concerning Denmark that were retrievable using ‘One Health’ as the key search term. Three searches in two databases yielded 30 retrieved publications, 13 of which were included in the review. The included publications had been published between 2015 and 2021. Twelve of the publications were co-authored in collaboration across institutes from different sectors. Three of the publications had focus on antimicrobial resistance, and three on disease surveillance and/or control. Five of the publications were assessments or evaluations. The overall number of publications identified by a search using ‘One Health’ as the key search term was limited. Using the expression as keyword could help making One Health research more easily findable and allow to obtain an overview of research in the field.